Young infants process prediction errors at the theta rhythm - Köster, Moritz; Langeloh, Miriam; Michel, Christine; Hoehl, Stefanie (NeuroImage, 2021)
Examining how young infants respond to unexpected events is key to our understanding of their emerging concepts about the world around them. From a predictive processing perspective, it is intriguing to investigate how the infant brain responds to unexpected events (i.e., prediction errors), because they require infants to refine their predictions about the environment. Here, to better understand prediction error processes in the infant brain, we presented 9-month-olds (N = 36) a variety of physical and social events with unexpected versus expected outcomes, while recording their electroencephalogram (EEG). We found a pronounced response in the ongoing 4-5 Hz theta rhythm for the processing of unexpected (in contrast to expected) events, for a prolonged time window (2 s) and across all scalp-recorded electrodes. The condition difference in the theta rhythm was not related to the condition difference in infants’ event-related activity to unexpected (versus expected) events in the negative central (Nc) component (0.4-0.6 s), a component, which is commonly analyzed in infant violation of expectation studies using EEG. These findings constitute critical evidence that the theta rhythm is involved in the processing of prediction errors from very early in human brain development. We discuss how the theta rhythm may support infants’ refinement of basic concepts about the physical and social environment.
Gesehen am 17.09.2021